Chemical process equipment : selection and design - Couper, James R. (Elsevier/Butterworth-Heinemann, 2010)
A facility is only as efficient and profitable as the equipment that is in it. This highly influential book is a powerful resource for chemical, process, or plant engineers who need to select, design or configure plant successfully and profitably. Written by some of the most experienced and well-known chemical and process engineers in the industry today, this information-packed volume gives the chemical or process engineer or engineering student all of the guidelines for the design and selection of chemical process equipment. Comprehensive and practical, its scope and emphasis on rea.